Design a better business : new tools, skills and mindset for strategy and innovation - Pijl, Patrick van der; Lokitz, Justin; Solomon, Lisa Kay (Wiley, 2016)
How to use this book: 8 Chapters; 48 Case studies; 20 Tools; 7 Core skills;Designers; 36 Hacks; >150 Visuals